PENGARUH PERSEPSI DUKUNGAN ORGANISASI INTERNAL TERHADAP KOMITMEN AFEKTIF UNTUK BERUBAH: (STUDI PADA BAGIAN ORGANISASI DI SEKRETARIAT DAERAH KABUPATEN KERINCI) - Herlina, Vivi (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2021)
The purpose of this study was to determine whether there is an influence of internal organizational support perception toward affective commitment to change the employees of the Sekretariat Daerah Kabupaten Kerinci. As an independent variable, namely organizational support and the dependent variable is the affective commitment to change. The sampling process using a questionnaire which further calculation process validity test and reliability test. The analytical method used is linear regression and t-test to determine the magnitude of the influence between the internal organizational support perception for affective commitment to change. The linear regression equation of the results obtained was Y = 29.348 + 0.328X. The result of t-test value was 4.115 and the t-table is 1.668. Because the t value is greater than t-table, this indicates that there is a significant influence between the variables of Internal Organizational Support Perception on Affective Commitment to Change